Формування культури ділового спілкування у майбутніх лікарів у закладах вищої освіти - Качайло, Костянтин Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2025)
У дисертації здійснено теоретичний аналіз проблеми та запропоновано нове вирішення наукового завдання, яке полягає у виявленні, теоретичному обґрунтуванні педагогічних умов та експериментальній перевірці їх впливу на сформованість культури ділового спілкування майбутніх лікарів у закладах вищої освіти. Об’єкт дослідження – процес професійної підготовки майбутніх лікарів у закладах вищої освіти. Предмет дослідження – педагогічні умови формування культури ділового спілкування майбутніх лікарів. Метою дослідження є виявлення впливу науково обґрунтованих і експериментально перевірених педагогічних умов формування культури ділового спілкування у майбутніх лікарів у закладах вищої освіти на рівень сформованості означеної якості. Dissertation for the degree of Doctor of Philosophy in specialty 011 “Educational, Pedagogical Sciences”. – National Technical University “Kharkiv Polytechnic Institute”, Ministry of Education and Science of Ukraine, Kharkiv, 2025. The dissertation provides a theoretical analysis of the problem and proposes a new solution to the scientific task, which consists in identifying, theoretically substantiating pedagogical conditions and experimentally verifying their influence on the formation of a culture of business communication among future doctors in higher education institutions. The object of the study is the process of professional training of doctors in a higher education institution. The subject of the study is the pedagogical conditions for the formation of a culture of business communication of future doctors in higher education institutions. The purpose of the study is to identify the influence of scientifically substantiated and experimentally proven pedagogical conditions for the formation of a culture of business communication among future doctors in higher education institutions on the level of formation of the specified quality.
Formation of a culture of business communication among future doctors in higher education institutions
Keywords: майбутній лікар; культура ділового спілкування; фахова підготовка; формування; соціальні навички; навчально-методичний інструментарій; future doctor; culture of business communication; professional training; formation; social skills; educational and methodological tools